Changes in Non-Volatile Compounds and Extracts of Wines Due to Yeast Species and Fermentation Temperature - Ough, C. S.; Winger, C. L. (South African Journal of Enology and Viticulture, 2017)
The real reducing sugar-free extracts and the calculated extracts of wines vary significantly with fermentation temperature within the range of l2°-2l°C. Relevant compositional changes are shown and discussed. The three yeasts used did not cause any significant difference in the calculated extracts. The conclusions were that any critical assessment of wine or juice amelioration based only on these forumulas would be subject to criticism.